Ectopic mammary tissue in vulva - Đorđević Momčilo; Jovanović Božidar; Mitrović Slobodanka; Đorđević Gordana (Vojnosanitetski Pregled)
Background. Ectopic mammary gland tissue is a residual tissue that persists during the embryologic development along ectodermal primitive milk streaks. Incomplete involution anywhere along the primitive milk streak can result in accessory or ectopic mammary tissue. Case report. A woman, 27-year old, admitted to Obstetrics and Gynecology Clinic Kragujevac for surgery, of goose-egg size, vulva tumor, of elastic consistency. Menarche started in 12 years of age, with the regular menstrual cycle, without previous gynecological diseases. The woman had one pregnancy terminated by cesarean section because of the multiple (twin) pregnancy. Excision of the tumor was completely done in the total endotracheal anesthesia. Pathohistologic (PH) findings was: Dysplasia fibrosa cystica simplex mammae, with focuses of sclerosing adenosis. Expression of estrogen (ER) and progesterone receptors (PR) were positive. Conclusion. Ectopic mammary tissue in vulva in adult period is very rarely seen, and can be changed pathologically as well as normally positioned breast tissue into benign cystic changes, benign tumors, adenomas and fibroadenomas and tumors. Cells with low ER/PR receptor level grow independently of estrogene stimulation and they could be resistant to hormonal therapy effects.